2023
DOI: 10.1007/s11230-023-10127-y
|View full text |Cite
|
Sign up to set email alerts
|

Description of new species of Trematoda from bats of Southeastern Mexico and a new classification for Brachylecithum rileyi n. comb. (Dicrocoeliidae)

Wilson I. Moguel-Chin,
Jesús Alonso Panti-May,
Brenda Atziri García-García
et al.

Abstract: To date, 23 species of trematodes have been reported in bats from Mexico. However, in some regions of Mexico, such as the Yucatan Peninsula, many species of bats do not have helminthological records. Here, we sampled bats in four localities in Southeastern Mexico from April 2017 to February 2022. Parasites were collected from the intestine of four species of bats: Pteronotus fulvus, Eumops nanus, Noctilio leporinus and Nyctinomops laticaudatus. Conventional morphological techniques and molecular tools with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…There has been a recent increase in studies of bat helminths in the Neotropics, in some contrast to the lack of recent similar studies in the Nearctic (Achatz et al, 2018 , 2020 ; Tkach et al, 2018 , 2019 ; Fernandes et al 2019 , 2021a , b , 2022 ; Panti-May et al, 2021 ; Moguel-Chin et al, 2023 , 2024 ; Kinsella et al, 2024 ). All these studies have invariably demonstrated that the helminth fauna of bats in the Western Hemisphere remains understudied and that these hosts likely harbor a much richer fauna of helminth parasites than currently known.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent increase in studies of bat helminths in the Neotropics, in some contrast to the lack of recent similar studies in the Nearctic (Achatz et al, 2018 , 2020 ; Tkach et al, 2018 , 2019 ; Fernandes et al 2019 , 2021a , b , 2022 ; Panti-May et al, 2021 ; Moguel-Chin et al, 2023 , 2024 ; Kinsella et al, 2024 ). All these studies have invariably demonstrated that the helminth fauna of bats in the Western Hemisphere remains understudied and that these hosts likely harbor a much richer fauna of helminth parasites than currently known.…”
Section: Discussionmentioning
confidence: 99%